2022
DOI: 10.1021/acs.iecr.2c02416
|View full text |Cite
|
Sign up to set email alerts
|

Tacticity and Ionization Effects on Adsorption Behavior of Poly(acrylic acid) and Poly(methacrylic acid) at the CCl4–H2O Interface Revealed by MD Simulations

Abstract: Atomistic molecular dynamic simulations were performed to investigate the adsorption behavior of poly(acrylic acid) (PAA) and poly(methacrylic acid) (PMA) at the CCl4–H2O interface for isotactic, atactic, and syndiotactic forms. The conformational, orientation, and solvation behaviors of PAA and PMA chains at the interface were studied as a function of the degree of ionization (f). The calculated density profiles show that adsorption occurs only when degree of ionization is less than a critical value (ionizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 104 publications
0
6
0
Order By: Relevance
“…The GROMOS96 force field was shown to yield results in good agreement with experimental behavior for PAA and PMA in bulk aqueous solution 52 as well as at the CCl 4 -water interface. 42 The aliphatic atoms of the polymer are represented as united atoms in this force field and help in reducing the computational cost when compared to all-atom models. The SPC/E model gives accurate hydration free energies for amino acids and solution properties of polymers.…”
Section: System Setup and Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…The GROMOS96 force field was shown to yield results in good agreement with experimental behavior for PAA and PMA in bulk aqueous solution 52 as well as at the CCl 4 -water interface. 42 The aliphatic atoms of the polymer are represented as united atoms in this force field and help in reducing the computational cost when compared to all-atom models. The SPC/E model gives accurate hydration free energies for amino acids and solution properties of polymers.…”
Section: System Setup and Methodologymentioning
confidence: 99%
“…40 MD and DFT simulations showed that isotactic poly(methacrylic acid) adsorbs at the CCl 4 -water interface, and is hydrophobic, in agreement with VSFS experiments. 41,42 Coarse-grained MD simulations showed a change in the morphology of aggregates of poly(styrene)block-poly(2-vinylpyridine) chains at the chloroform-water interface in going from loosely packed to densely packed structure with the increase in the change fraction of the polymer. 43 Hydrophobic interactions are considered to be the major driving force for adsorption of amphiphilic molecules, such as proteins and surfactants, at the oil-water interface.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This capability enables the theoretical evaluation of the interface interaction mechanisms of bonding agents and facilitates targeted development. In recent years, MD methods have been widely applied in various fields to investigate material mechanics, separation processes, adsorption phenomena, and diffusion characteristics. Especially in propellants, Wang et al discussed the phase separation process of NPBA in a nitrate system. Zheng et al used the MD method to study the rheological behavior of the HTPB binder on the surface of Cu/Al nanoparticles.…”
Section: Introductionmentioning
confidence: 99%